1998
DOI: 10.7326/0003-4819-128-4-199802150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Chlamydia trachomatis in Asymptomatic Women Attending Family Planning Clinics: A Cost-Effectiveness Analysis of Three Strategies

Abstract: These results suggest that age-based screening provides the greatest cost savings of the three strategies examined. However, universal screening is desirable in some situations. In general, screening done by using any criteria and a highly sensitive diagnostic assay should be part of any chlamydial prevention and control program or health plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 30 publications
3
71
1
2
Order By: Relevance
“…Previous studies have demonstrated that screening programs for STDs are cost-effective in direct proportion to the number of infections that are detected and treated before infection is transmitted or sequelae develop (10,21,22,24). The higher the predictive value of the test, both positive and negative, the greater the value of testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that screening programs for STDs are cost-effective in direct proportion to the number of infections that are detected and treated before infection is transmitted or sequelae develop (10,21,22,24). The higher the predictive value of the test, both positive and negative, the greater the value of testing.…”
Section: Discussionmentioning
confidence: 99%
“…With the more sensitive tests, the return on the public health investment in screening programs is higher. A study of the cost-effectiveness of screening for C. trachomatis using culture, direct tests, and amplification tests suggested that the amplification tests provided the greatest cost benefit by permitting noninvasive specimen collection and preventing the greatest number of PID cases (20,23,24).…”
mentioning
confidence: 99%
“…Maryland Medicaid reimburses $28 per cervical chlamydia PCR test, but reimbursement may differ by state and insurance scheme. 54 Chlamydia screening of sexually active adolescent females in both primary care and nontraditional health care settings detects a large burden of asymptomatic infection in a variety of demographically defined populations. 33,37,49,50 We demonstrated that the median time to diagnosis of incident infection is approximately 6 months, regardless of prior infection status, and that selective screening criteria are unable to identify a group in which to target screening efforts among adolescent females.…”
Section: -41mentioning
confidence: 99%
“…Because most infected individuals are either asymptomatic or have mild, nonspecific symptoms, C. trachomatis infection poses a problem for health control programs. National screening and prevention programs for C. trachomatis infection have been implemented, usually among young adults, in industrialized countries (11,14,16). With the exception of sporadic testing of commercial sex workers, Chlamydia screening is rare in developing countries, which have the highest incidence of new chlamydial infections (7,9,17,25).…”
mentioning
confidence: 99%